GAMBARAN PENANGANAN MANDIRI IBU HAMIL DENGAN EMESIS GRAVIDARUM PADA TRIMESTER I DI BKIA RUMAH SAKIT WILLIAM BOOTH SURABAYA - ., Intyaswati, Maria Martina (D3 Kebidanan, 2013)
Nausea and vomiting is one of the earliest symptoms, most common and most important as a cause of stress associated with pregnancy. Most of the pregnant woman will try to cope with symptoms of nausea and vomiting themselves how they feel. Habits of pregnant women who solve their own problems of nausea and vomiting, sometimes consciously or unconsciously, may endanger the health of mother and fetus. In fact, pregnant women will try to consume everything, which is expected to reduce nausea and vomiting. On this note, good nutrition is almost irrelevant to the treatment of nausea and vomiting. Based on these problems, researchers are conducting research on